2016
DOI: 10.1016/j.ophtha.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Natural History of Dry Eye Disease from the Patient's Perspective

Abstract: Objective The goal of this study is to describe the natural history of Dry Eye Disease (DED), which chronically affects millions of people in the US alone. Design This study includes cohorts from the Women's Health Study (WHS) and Physicians' Health Studies (PHS), and utilizes a combination of cross-sectional surveys and review of existing medical records. Participants 398 men from the PHS and 386 women from the WHS who reported they had DED and responded to a questionnaire about change in various aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 19 publications
1
36
0
1
Order By: Relevance
“…Improvement was reported by 44% of respondents for ocular surface symptoms, 19% for vision-related symptoms, and 19% for social impact, while worsening since diagnosis was reported by 24%, 29%, and 10%, respectively. 9 While ocular lubricants are a mainstay of DED therapy, they generally provide only temporary symptom relief and do not target the underlying pathophysiology of DED. 1 Numerous formulations are available.…”
Section: Limitations Of Current Ded Treatmentmentioning
confidence: 99%
“…Improvement was reported by 44% of respondents for ocular surface symptoms, 19% for vision-related symptoms, and 19% for social impact, while worsening since diagnosis was reported by 24%, 29%, and 10%, respectively. 9 While ocular lubricants are a mainstay of DED therapy, they generally provide only temporary symptom relief and do not target the underlying pathophysiology of DED. 1 Numerous formulations are available.…”
Section: Limitations Of Current Ded Treatmentmentioning
confidence: 99%
“…This finding is in contrast to a randomized study of artificial tears vs cyclosporine, 0.05%, where 32% of 22 patients treated with artificial tears had disease progression (composite of symptoms and signs) at 1 year vs 6% of 36 patients treated with cyclosporine, 0.05%. 26 A previous study demonstrated that patients with neuropathic pain-like ocular symptoms (hot-burning ocular pain and sensitivity to light and wind) had a more persistent and severe course of dry eye symptoms. 27 A limitation of that study, however, was that these pain-specific descriptors were obtained at follow-up and not at the baseline examination.…”
mentioning
confidence: 99%
“…Clinical observations and impressions suggest that DED may be a progressive disorder. Lienert et al reported worsening of DED symptoms over time (13) and Rao et al have reported DED progression (worsening of signs and symptoms) in a proportion of patients (14). The DEWS II definition of DED does not include progression.…”
mentioning
confidence: 99%